Penggunaan Subject-Verb Agreement dalam Menulis Text Bahasa Inggris - Anita Sari; Wirhayati Wirhayati; Kanaya Ratu Vanisa; Tasya Aulia Hidayati; Desthalita Rafni Azzakiya; Poppy Dwidia Gustanti; Amanda Amelia Putri (Jurnal Pendidikan dan Pengabdian Masyarakat, 2026)
Writing ability in English particularly subject-verb agreement requires strong grammar mastery as the core of constructing correct sentences. However, the eighth grade of junior high students in Pondok Pesantren Modern Al-Ghozali, Gunung Sindur have difficulty in using Subject -Verb Agreement, particularly in the present tense and present progressive tense. The causes of having much more theories and lacking of writing practice in English make them have low understanding and confidence in using English in the class. This Community Service (PKM) is aimed to enhance students’ understanding in Grammar, to improve students writing in English, and to build their confidence through interactive and applied learning. The method was conducted through observation, pre-test, presentation delivery, interactive game, error analysis, writing practice, and post test. The material is focusing on the use of subject-verb agreement in writing English text. The activity was conducted on Sunday, 12 April 2026 at Pondok Pesantren Modern Al-Ghozali, Gunung Sindur, Bogor. The results show a significant improvement in students’ understading indicated by the rise in the average pre-test score from 45% to 76% at the stage of error analysis, and a further increase to 85% in the post-test, representing a total improvement of 40%. These findings imply that an interactive teaching approach combined with error analysis is effective in enhancing students’ ability to apply subject-verb agreement rule in English text.